Selected Aspects of Age Management as a Challenge for Polish Entrepreneurs - Monika Sipa; Andrzej SkibiÅ„ski (Journal of Education and Vocational Research, 2016)
The process of demographic aging is not only a long-term threat to the maintenance of social security systems, but also a major challenge for the companies in terms of the HR function implementation. It is necessary that employers take a more responsible attitude to the problems of an aging population in order to provide the proper functioning not only of these organisations, but also of the whole society and economy. This paper presents some aspects of age management in the context of the perception of this problem by Polish employers. The main objective of this elaboration was to determine whether and how Polish organisations view the problem of aging of labour force.